Changes in Swedish spruce forests since 1986 from a reindeer husbandry perspective - Lundgren, Sara (2020)
Loss of important reindeer habitats is an increasing concern in Sweden. The focus for loss of habitats has mainly been pine (Pinus sylvestris L.) forests and lichens. However, reindeer diets also consist of other food sources like sedges, grasses and herbs (often found in spruce forests) that will be discussed in this study. There has been a decline of spruce (Picea spp.) forests within the reindeer husbandry area and the importance of those habitats for reindeers has been neglected through planning in favour of lichen rich pine stands. The aim of this study is to describe the change of spruce forests within the reindeer husbandry area with focus on changes over time in field layer, age distribution and relative stocking level. As well as performing a statistical analysis on the relationship between field-layer and relative stocking level or age distribution. This study is centred around two main questions: What explains the results and how does it affect the reindeer? The results from this study has shown a change in age distribution, relative stocking level and a large total area decrease of spruce forests within the reindeer husbandry area since 1986. The results also show a significant association between herbs/grass and relative stocking level through statistical tests. There is also a significant relationship between grass and forest age.